AUTOANTIBODIES IN SYSTEMIC SCLEROSIS: SPECTRUM, CLINICAL ASSOCIATIONS, AND PROGNOSTIC VALUE - L. P. Ananyeva; E. N. Aleksandrova (Научно-практическая ревматология, 2016)
The purpose of the review is to clinically evaluate circulating autoantibodies in systemic sclerosis (SS). The diseasespecific, i.e. disease-associated, antinuclear autoantibodies: to centromeres, to topoisomerase 1; a group of antinuclear antibodies to ribonucleoprotease III, Th/T0, Pm/Scl, as well as autoantibodies to ribonucleoproteins U1 RNP and U3 RNP are considered in detail. The detection rate of the antinuclear autoantibodies is high (90–95%); at the same time, each of the autoantibodies is detectable separately in a small number of patients with certain clinical presentation, patterns of the course, and prognosis and has clear genetic associations. There is a clear association between the type of autoantibodies, the nature of organic complications, and survival rates. Specific autoantibodies belong to predictors for the course of the disease and its outcome. How much the clinical distinctions between the subgroups reflect pathogenetic differences in immune dysregulation remains unclear. SS-specific autoantibodies emerge in the earliest stage of the disease until the clinical picture of the disease becomes extensive. Their diagnostic value and place in the 2013 new classification criteria for the disease are described in detail. There is evidence that it is important to introduce the determination of anti-centromere, anti-topoisomerase autoantibodies and anti-RNA proteinase III antibodies into clinical practice. The detection of the latter is essential due to the importance of identifying a special subtype of SS, which has a potentially poor prognosis, among other factors, due to the increased incidence of cancers. When making the SS diagnosis, it is appropriate to indicate its positivity for main scleroderma autoantibodies.The last section of the review deals with the non-specific autoantibodies directed against targets, such as endothelial cells and fibroblasts, functional molecules (different cell receptors), extracellular matrix proteins, enzymes, etc. A number of interesting hypotheses and theories, which explain the initiating role of this subgroup of autoantibodies in the occurrence and development of SS, are considered.